A systematic review on the anthropogenic stressors on sessile benthic mesophotic reef communities: implications for temperate reef management in Australia - Wong, Rachel H. X.; Monk, Jacquomo; Perkins, Nicholas R.; Barrett, Neville S. (Frontiers in Marine Science, 2023)
Temperate rocky reefs are complex habitats that support high levels of biodiversity and productivity. However, the sessile benthic communities attached to these reefs are vulnerable to climate change and local human impacts due to their limited capacity to rapidly avoid unfavourable environments. In southeastern Australia, high latitude rocky reefs face increasing threats from rapid warming, surpassing the global average. Existing management efforts for these reefs rely heavily on research from tropical coral ecosystems and shallow temperate algaldominated rocky reefs, where sufficient data allows for reliable predictions on the future state of the systems. Recent evidence from seabed mapping programs indicates that mesophotic reefs (~30-150 m depth) are equally or more extensive than shallow systems in temperate waters. They provide novel ecosystem functions and could potentially act as climate refuges for some components of shallow water communities that extend across depth strata. However, despite their importance, very little is known about the threats faced by non-algal sessile organisms in either shallow water or mesophotic systems in many parts of the world, including temperate Australia. This review examined the current state of knowledge regarding the direct impact of physical disturbances, such as extreme weather events, ocean warming and destructive fishing practices, on sessile mesophotic communities in general. We then used this to infer the likely drivers of change in temperate mesophotic systems. We found that Australia's temperate mesophotic ecosystems were less likely to be impacted by fishing, anchoring and lost fishing gears compared to the northern hemisphere due to lower population density. Instead, we identified present and future pulsed warming events and severe storms as major threats to Australia's mesophotic systems. This conclusion is based on the lack of evidence supporting the existence of depth refuges from climate events in the current literature and the potential implications of the predicted future increases in high wind-wave energy and warming extending into the mesophotic depths. Drawing from observations globally, changes in the distribution of growth forms, size or diversity of sponges may be useful indicators of heat stress and seabed disturbances in temperate mesophotic systems.